The tale of two windy cities: public attitudes towards wind farm development - Bond, Sandy (School of Economics and Finance, Curtin Business School, 2009)
The Australian government is supporting the development of renewable energy technology, such as wind power, in its efforts to reduce greenhouse gases in line with the Kyoto agreement. While wind technology offer many advantages property owners have voiced opposition to the siting of wind farms due to concerns over changes in neighborhood aesthetics, noise, loss of bird life, and loss in property values. Such opposition can result in planning permission being declined and a restriction in the ability to meet Kyoto targets. This paper outlines the results of research carried out in Western Australia in 2008 to investigate the attitudes of residents from two southern coastal towns towards the development of wind farms. The results indicate that overall the respondents from both Albany and Esperance think of a wind farm in positive terms. The proximity to the wind farm is an important aspect that could determine attitudes with many respondents reporting that they would not want to live "near" a wind farm (usually stated as between 1-5km). Over a third (38%) of the respondents would pay 1%-9% less for their property due to the presence of a wind farm nearby. These results will be of interest to power companies in helping plan the siting of wind farms.